2005
DOI: 10.1002/adma.200500614
|View full text |Cite
|
Sign up to set email alerts
|

Porous Nanoparticle Membranes: Synthesis and Application as Fuel‐Cell Catalysts

Abstract: S2 1Àcaa measured 1Àcaa complete (1) was calculated from the axial ratio (c/a) measured , where c and a are the lattice parameters of the tetragonal phase, evaluated from FePt (001) and FePt (110) peaks. The axial ratio for fully ordered-L1 0 fct phase (c/a) complete for FePt is 0.9657. Magnetic properties were characterized at room temperature, in a Lake Shore 7400 vibrating samples magnetometry (VSM) instrument using applied magnetic fields up to 2000 mT. The hysteresis loops were measured on the nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 38 publications
1
38
0
1
Order By: Relevance
“…Both electrodes exhibit a current decay during the initial period because of the formation of intermediate species such as CH 3 OHads and CHOads, which is similar to the observations previously recorded for traditional Pt and PtRu catalysts. [36][37][38] The long time decay has been attributed to the adsorbed SO 2À 4 anions on the catalyst surface, which tend to inhibit the oxidation of methanol. Nevertheless, the Pt-CNT-Pt structures exhibit a current density of 0.518 mA mg À1 at 1000 s, which is eight times higher than the corresponding value for Pt-XC72, which shows a current density of 0.061 mA mg À1 at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…Both electrodes exhibit a current decay during the initial period because of the formation of intermediate species such as CH 3 OHads and CHOads, which is similar to the observations previously recorded for traditional Pt and PtRu catalysts. [36][37][38] The long time decay has been attributed to the adsorbed SO 2À 4 anions on the catalyst surface, which tend to inhibit the oxidation of methanol. Nevertheless, the Pt-CNT-Pt structures exhibit a current density of 0.518 mA mg À1 at 1000 s, which is eight times higher than the corresponding value for Pt-XC72, which shows a current density of 0.061 mA mg À1 at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…[93] Teng et al showed that free-standing nanoporous membranes of single and multiple layer c-Fe 2 O 3 nanoparticles could be generated by combining the LB technique with AAO templates. [94] In a typical process, oleic acid stabilized c-Fe 2 O 3 nanoparticles were deposited as a monolayer or multilayer on the surface of an AAO membrane using the LB technique. After deposition, the sample was carbonized at elevated temperatures in a tube furnace.…”
Section: Templating Against Anodic Aluminum Oxide Membranesmentioning
confidence: 99%
“…Due to its low cost and the abundance of its raw materials in nature, Fe 2 O 3 has been widely investigated in many technological fields for applications such as energy materials for lithium ion storage, gas sensors, catalysts, and magnetic applications [1][2][3][4][5][6]. It is well known that the particle sizes and shapes of nanoscale materials affect their properties and potential applications.…”
Section: Introductionmentioning
confidence: 99%